A New Perspective of Literary Criticism - Deng Jun (Lingua Cultura, 2009)
Paratext is a relatively new term in literary criticism, which is mainly elaborated by modern French scholar Gérard Genette. Article presents a qualitative method with its purpose to present a survey to this new literary term and probe into what may lie behind this new critic perspective. Analysis was done by exploring the new literatures in terms of paratext. It can be concluded that paratext has a great influence to the deeper understanding from different perspectives of a literature work.